Cross-sectional study of older adults with type 2 diabetes mellitus in two rural primary healthcare facilities in Malaysia. - Ooi, Cheow Peng; Loke, Seng Cheong; Ahmad, Zaiton; Tengku Abdul Hamid, Tengku Aizan; Yassin, Zaitun (2011)
Knowledge of the characteristics of older adults with type 2 diabetes mellitus (T2DM) is indispensible for improvement of their care. A cross-sectional study in two rural public primary healthcare centres in Malaysia identified 170 actively engaged older patients with T2DM, with suboptimal glycaemic control and frequent hypoglycaemia. The prevalence of multiple co-morbidities, complications of T2DM, high cardiovascular risk, neurological, musculoskeletal and visual deficits suggested high risk of disabilities and dependency but not yet disabled. This short window for interventions presents as an opportunity for development of a more comprehensive approach extending beyond glycaemia control to risk management, preventing functional loss and continuity of social participation.